The Role of Local Government in Supporting Community-Based Green Economy Transition - Hastuti Handayani Harahap (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze the role of local governments in supporting a community-based green economy transition, focusing on policy implementation, community participation, and its impact on welfare and environmental sustainability. The method used in this study is a descriptive qualitative approach with data collection techniques through literature studies, interviews, observation, and documentation. The results show that local governments have a strategic role as regulators, facilitators, motivators, and innovators in encouraging green economy development at the local level. The implementation of green economy policies is realized through strengthening environmentally-based MSMEs, digitalizing the community economy, and community-based empowerment programs. Community participation in green economy programs shows a significant increase, especially in environmental management activities, developing environmentally friendly businesses, and utilizing digital technology. In addition, the implementation of the green economy has a positive impact on increasing community income, creating new jobs, and increasing environmental awareness. However, several challenges remain, such as limited community literacy, infrastructure support, and policy coordination. Therefore, synergy is needed between local governments, communities, and the private sector to strengthen the implementation of a sustainable and inclusive green economy.